2018
DOI: 10.12688/f1000research.14836.3
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in the proinflammatory activity of urban fine particulate matter (PM2.5) by in vitro assays

Abstract: Background: Ambient particulate matter (PM) smaller than 2.5 µm in diameter (PM 2.5) undergoes diurnal changes in chemical composition due to photochemical oxidation. In this study we examine the relationships between oxidative activity and inflammatory responses associated with these diurnal chemical changes. Because secondary PM contains a higher fraction of oxidized PM species, we hypothesized that PM 2.5 collected during afternoon hours would induce a greater inflammatory response than primary, morning PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…[45,46] Similar effects were observed in studies of primary rat microglia using a smaller particle size after both acute (<24 h) and chronic (<7 days) treatments [47,48] and in a microglial cell line with acute treatment using PM2.5. [49][50][51] Primary mixed glial cultures and microglial cell line experiments suggest that PM activate proinflammatory gene expression via toll-like receptor 4/NF-κB signaling. [52][53][54][55] Co-cultures of primary microglia with rodent cerebellar granule [45] or cortical [46,56,57] neurons have established that exposure to DEP and/or PM 2.5 (and subsequent proinflammatory cytokine production) reduced neurite outgrowth and increased neurotoxicity by and reduced the expression of proinflammatory cytokines (pioglitazone, minocycline) had neuroprotective roles.…”
Section: Pm Exposure Results In Microglial Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…[45,46] Similar effects were observed in studies of primary rat microglia using a smaller particle size after both acute (<24 h) and chronic (<7 days) treatments [47,48] and in a microglial cell line with acute treatment using PM2.5. [49][50][51] Primary mixed glial cultures and microglial cell line experiments suggest that PM activate proinflammatory gene expression via toll-like receptor 4/NF-κB signaling. [52][53][54][55] Co-cultures of primary microglia with rodent cerebellar granule [45] or cortical [46,56,57] neurons have established that exposure to DEP and/or PM 2.5 (and subsequent proinflammatory cytokine production) reduced neurite outgrowth and increased neurotoxicity by and reduced the expression of proinflammatory cytokines (pioglitazone, minocycline) had neuroprotective roles.…”
Section: Pm Exposure Results In Microglial Activationmentioning
confidence: 99%
“…[ 45,46 ] Similar effects were observed in studies of primary rat microglia using a smaller particle size after both acute (<24 h) and chronic (<7 days) treatments [ 47,48 ] and in a microglial cell line with acute treatment using PM2.5. [ 49–51 ] Primary mixed glial cultures and microglial cell line experiments suggest that PM activate proinflammatory gene expression via toll‐like receptor 4/NF‐κB signaling. [ 52–55 ]…”
Section: Chronic Neuroinflammation Following Exposure To Pm Is Mediated By Glial Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is nitric oxide signaling and the potential regulatory role of nitric oxide synthase during nPM-mediated neurotoxicity. Our prior studies showed that nPM induces iNOS, nitric oxide, and/or nitrosylation in cell culture [ 56 , 57 ], hippocampal slice [ 30 ], and in vivo [ 56 ]. Our analyses identified a subset of 322 nPM-DEGs in the female neonatal cerebral cortex after gestational exposure to nPM.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using PM2.5 collected in the morning and afternoon, more proinflammatory activity as revealed by nitric oxide(NO) induction in cells exposed to morning PM. The upregulation of proinflammatory cytokines IL-1β, IL-6, and CCL2(MCP-1) was observed, which indicated aging reduced toxicity [174] .…”
Section: Effects Of Atmospheric Aging Processesmentioning
confidence: 99%